2014
DOI: 10.1039/c3mb70199a
|View full text |Cite
|
Sign up to set email alerts
|

Role of cytoskeletal proteins in cerebral cavernous malformation signaling pathways: a proteomic analysis

Abstract: An in vitro proteomics and systems biology of cerebral cavernous malformation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 43 publications
0
6
0
1
Order By: Relevance
“…However, p53 expression remained largely unaltered in TRIM59 KD MCF7 cells, thus clearly indicating the existence of a p53-independent mechanism. Notably, proteomic mapping of PDCD10 interactors has identified proteins involved in the regulation of G0/G1-S phase transition of the cell cycle, such as cytoskeletal protein guanine nucleotide-binding protein subunit beta-like protein (GBLP) [ 14 , 64 ]. Further analysis is needed to clarify whether PDCD10 is directly responsible for the function of TRIM59 in cell survival and cell cycle regulation.…”
Section: Discussionmentioning
confidence: 99%
“…However, p53 expression remained largely unaltered in TRIM59 KD MCF7 cells, thus clearly indicating the existence of a p53-independent mechanism. Notably, proteomic mapping of PDCD10 interactors has identified proteins involved in the regulation of G0/G1-S phase transition of the cell cycle, such as cytoskeletal protein guanine nucleotide-binding protein subunit beta-like protein (GBLP) [ 14 , 64 ]. Further analysis is needed to clarify whether PDCD10 is directly responsible for the function of TRIM59 in cell survival and cell cycle regulation.…”
Section: Discussionmentioning
confidence: 99%
“…TCPB, which serves as a molecular chaperon by assisting the folding of proteins upon the adenosine triphosphate (ATP) hydrolysis, is known to play a role in actin and tubulin formation in vitro [ 70 ]. Although this study presented TCPB down-regulation in high doxorubicin-resistant FISS, there is only one other study presenting its down-regulation in TS1-resistant pancreatic cancer cells, which indicates their role in chemosensitivity for TS1—a novel oral anticancer agent containing two biochemical modulators for 5-fluorouracil (5-FU) and tegafur, a metabolically activated prodrug of 5-FU [ 71 ].…”
Section: Discussionmentioning
confidence: 99%
“…CCM proteins directly interact with each another to form a CCM1-CCM2-CCM3 based signaling platform (68 , 69) with interacting proteins rather distinct for each CCM protein (19 - 21 , 70 - 72) . Interaction between CCM2 and CCM3 is necessary for stability of the two proteins (73) and CCM2 dependent stabilization of CCM1 has also been reported (49) .…”
Section: Formation Of a Heterotrimeric Ccm1-ccm2-ccm3 ‘Ccm Complex Simentioning
confidence: 99%
“…1 ). Indeed, both in vivo and in vitro studies revealed that perturbation of the WNT/β-catenin pathway (10 , 11) , TGF-β/BMP (10 , 12 , 13) and Notch signaling (14) , cytoskeletal regulation (8 , 15) and anti-oxidant signaling (16 - 18) are responsible for CCM pathogenesis and several proteomic studies elegantly showed that all three ccm genes encode CCM proteins comprising distinct macromolecular complexes, implying complex regulation of multiple signaling pathways due to various interactions with many signaling molecules by each CCM protein (19 - 21) . As individual proteins comprising the distinct macromolecular CCM complexes are still not fully characterized, our understanding of the composition of the CCM macromolecular complexes and associated functional networks is still in its infancy.…”
Section: Introductionmentioning
confidence: 99%